FAKTOR-FAKTOR YANG MEMPENGARUHI KEJADIAN STUNTING DI DESA NGEMPLAK, KECAMATAN GEBANG KABUPATEN PURWOREJO - Zuliyanti, Nurma Ika; Setyaningsih, Evi; Cahyani, Indah Gita (Jurnal Kebidanan, 2024)
F FACTORS AFFECTING STUNTING INCIDENTS IN NGEMPLAK VILLAGE, GEBANG DISTRICT, PURWOREJO REGENCY ABSTRACT Background: Stunting is related to morbidity and mortality, decreased physical capacity, impaired development and function of children’s motor and mental conditions. Based on tabulation results that have been studied for one week, it was recorded that there were 52 toddlers and 9 of them were stunted, 2 were categorized as very short height and 6 were categorized as short, apart from stunting, 8 toddlers also experienced abnormal nutrition, 2 of them were in the category of poor nutrition, and 5 of them were with malnutrition and the other 4 have normal nutrition.Research objective: To find out the factors that influence the incidence of stunting in Ngemplak Village, Gebang District, Purworejo Regency. Research Method: This research is an analytical observational study with a cross sectional approach, a population of 52 mothers of toddlers and a sample of 23 mothers of toddlers. Purposive sampling technique. Collecting direct observation data on respondents used checklists and secondary data from KIA, KMS, DDST books. Chi Square statistical test techniques and Fisher’s test. Research Results: there is a relationship between economic status and the incidence of stunting (p value 0.021<0.05). There is a relationship between maternal education level and the incidence of stunting (p - value 0.027 < 0.05). There is a relationship between maternal height and the incidence of stunting (p - value 0.010 < 0.05). There is a relationship between exclusive breastfeeding and the incidence of stunting (p - value 0.034 < 0.05). There is a monitoring relationship. Conclusion: There is a relationship between economic status, maternal education, maternal height, exclusive breastfeeding, ANC monitoring and the incidence of stunting. Keywords: economic status, education, height, exclusive breastfeeding, ANC monitoring, stunting